2021
DOI: 10.3390/biomedicines9101409
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Cardiac Troponin Genes in Pediatric Patients with Heart Failure Supported by Ventricular Assist Device

Abstract: Ventricular Assist Device (VAD) therapy is considered as a part of standard care for end-stage Heart Failure (HF) children unresponsive to medical management, but the potential role of miRNAs in response to VAD therapy on molecular pathways underlying LV remodeling and cardiac function in HF is unknown. The aims of this study were to evaluate the effects of VAD on miRNA expression profile in cardiac tissue obtained from HF children, to determine the putative miRNA targets by an in-silico analysis as well as to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“… 3 Our previous study suggested that VAD heart unloading was able to modify the expression of specific microRNA (miRNAs) in HF pediatric patients. 9 The hsa-miR-1246, hsa-miR-199b-5p, and hsa-miR-19a-3p were differentially expressed after VAD implant and were able to regulate the expression of cardiac troponins. 9 In addition to sarcomere proteins, in silico analysis suggested the adiponectin (ADPN) system, including ADPN and its receptors, as a putative target of selected miRNAs ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“… 3 Our previous study suggested that VAD heart unloading was able to modify the expression of specific microRNA (miRNAs) in HF pediatric patients. 9 The hsa-miR-1246, hsa-miR-199b-5p, and hsa-miR-19a-3p were differentially expressed after VAD implant and were able to regulate the expression of cardiac troponins. 9 In addition to sarcomere proteins, in silico analysis suggested the adiponectin (ADPN) system, including ADPN and its receptors, as a putative target of selected miRNAs ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 95%
“… 9 The hsa-miR-1246, hsa-miR-199b-5p, and hsa-miR-19a-3p were differentially expressed after VAD implant and were able to regulate the expression of cardiac troponins. 9 In addition to sarcomere proteins, in silico analysis suggested the adiponectin (ADPN) system, including ADPN and its receptors, as a putative target of selected miRNAs ( Figure 1 ). 9 ADPN is an adipocyte-derived protein with the anti-inflammatory, anti-hypertrophic, anti-apoptotic, and anti-fibrotic role in the heart.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Comprehensive microarray profiling of miRNAs and mRNAs, comparing myocardial specimens from adults with end stage HF with VAD and nonfailing hearts, showed upregulation of 28 miRNAs with almost normalization of miRNA profiles by VAD treatment [117]. Cardiac miRNAs have also been compared in 13 HF children at pre-VAD and at the moment of heart transplant (post-VAD) by next-generation sequencing [118]. The investigators found hsa-miR-199b-5p, hsa-miR-19a-3p, and hsa-miR-1246 being differentially expressed at post-VAD compared to that at pre-VAD.…”
Section: Mirnas In Response To Lvad Therapymentioning
confidence: 99%